Pendampingan Baca Tulis Al-Quran untuk Meningkatkan Karakter Warga Rumah Tahanan (Rutan) Kelas II Kraksaan Probolinggo - M. Hasyim Syamhudi (GUYUB: Journal of Community Engagement, 2020)
The jail of grade 2 in Kraksaan Probolinggo East Java is inhabited by lots of prisoners with deviant behaviors and self-characters which are seemingly ignorant to accept a process of understanding Koran. It seems more difficult to a social stigma that the prisoners are far away religious truth, because their behaviors often frighten and make them to be normatively good people (shalihin and shalihat). Furthermore, a training program of Koran recitation for those who have no abilty of reading and writing Koran (baca-tulis Al-Quran) but have a high commitment of learning it is necessary. This traning is important because they are assumed as having split personality and need a persistent training. This traning is undertaken for a week, 1 – 7 November 2019.Keywords: The Jail of Grade 2 Kraksaan, Traning Program of Reading and Writing Koran, Prisoners’ Character